Conceptualisation of Grondkaart Regulation for Land Legal Certainty in Indonesia - Masykur, Mohammad Hamidi; Ganecha, Maulana Kasyfillah Syauqi; Mulyono, Ferio Ivan (Arena Hukum, 2025)
Land conflicts in Indonesia remain persistent, particularly disputes over Grondkaart lands controlled by Perseroran Terbatas Kereta Api Indonesia (PT KAI). The absence of explicit regulation in the Basic Agrarian Law (UUPA) and fragmented policy paradigms across institutions have led to legal uncertainty. Previous studies conducted by Karini (2021), Silvianna (2020), and Sulistiowati et al. (2020) examined Grondkaart as evidence of control or dispute resolution. However, they did not provide a comprehensive conceptualisation of permanent land rights for railway infrastructure. This research addresses that gap by analysing Grondkaart through the framework of Special Use Rights (Hak Pakai Khusus) as a sustainable legal solution. This normative juridical research uses statutory and conceptual approaches, focusing on the historical trajectory of Grondkaart from Dutch nationalisation and its problematic conversion into temporary Rights to Use. The findings show that granting PT KAI Special Use Rights with permanent validity provides stronger legal certainty than temporary rights, considering the permanent social function of railways. In practice, binding precedents and Supreme Court Circular Letters (SEMA) can guide judges in resolving disputes, though challenges persist in consistency and judicial understanding. This research recommends reforming agrarian law by affirming Special Use Rights for PT KAI as a permanent solution. Internationally, the article offers insights into post-colonial land disputes, showing how reconciling historical claims with present infrastructure needs can inspire reforms in other jurisdictions. The Indonesian case enriches global discourse on land rights and legal certainty, making it relevant to foreign scholars and policymakers.